Respon Pertumbuhan dan Produksi Sorgum (Sorghum bicolor [L.] Moench.) dengan Pemberian Berbagai Dosis Amelioran di Lahan Pasca Tambang Timah: Pengaruh Dosis Pupuk Kotoran Ayam dan NPK terhadap Pertumbuhan dan Hasil Tanaman Sorgum di Lahan Pasca Tambang Timah - Tri Lestari; Suharyanto Suharyanto; Suyipto Eko Pratomo (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Post tin mining land is one of marginal land because it has low nutrient availability. Efforts to utilize post tin mining land in agriculture for crop cultivation such as sorghum by application various doses of chiken manure an N,P,K. The purpose of this study was to determine the response of sorghum growth and production in post tin mining land by application various doses of chicken manure and N,P,K. This research used a factorial randomized block design with 6 treatment combinations and 4 groups. The first factor was the dose of chicken manure consisting of 100%, 50%, and 25% the reference dose. The second factor was the dose of fertilizer N, P, K which consists of 100% and 50% the reference dose. The results showed that chicken manure significantly affected leaves number parameters. Fertilizer N, P, K gave very significant effect on plant height, stem diameter, wet stover weight, root length, seed yield per plant and productivity. Fertilizers N, P, K significantly affect the total parameters of dissolved solids. The reduction of the dose of chicken manure from 100% to 50% showed no significant difference on leaves number. Reduction of N, P, K fertilizer doses showed significantly different results on all parameters. The A1K1 treatment (100% chicken manure + 100% N,P,K) is the best combination of treatment for the growth and production of sorghum in post tin mining land.